Modal and Path Contribution Models from In-Operation Data: Review and New Approaches. (2008) - Van der Auweraer, H.; Mas, P.; Peeters, P.; Janssens, K.; Vecchio, A.
Abstract : In several cases, laboratory-based modelling approaches such as Experimental Modal Analysis and Transfer Path Analysis run into limitations with respect to technical and economical feasibility (accessibility of the structure, excitation feasibility, measurement time, accuracy, …) as well as model representativity. Therefore, approaches such as in-operation modal analysis (OMA) have been developed and are reaching a similar degree of acceptability as standard EMA, with all limitations regarding accuracy and observability of the structural dynamics. In the same line of reasoning fits the question of system characterization and identification using (or based on) other operation data types such as transmissibility functions and coherence functions and data analysis procedures such as principal component analysis. Using these testing and analysis paradigms instead of the classical load-FRF-response one, key analysis techniques such as transfer path and contribution analysis can be reconsidered.